Coordinate Systems of the World : Datums And Grids - Mugnier, Clifford J. (Routledge, 2023)
"A comprehensive consolidation of data for the world, this book gives a short precis of each nation, each nation's history, its topography and a chronology of the development of geodetic surveying and coordinate systems for that specific nation. A starting point of information for understanding the world's datums and grids. Based on the details available for each nation, the reader is given an overall view that can answer questions regarding the sources of spatial information available, their limitations, and the critical things to be aware. The topographic maps compiled over the centuries represent the mixes of technology specifically to that nation. The book is a starting point for information and clues regarding existing maps and how those maps and coordinate systems were created"--